Chronic pain - a psychological approach - Maria da Graça Rodrigues Bérzin (Universidade Estadual de Campinas, 2015)
The article presents some relative considerations of bio-psycho-social nature to chronic pain, emphasizing to Temporomandibular Disorders (TMD). It describes some consequences triggered by chronic pain on the every life and points the main psychodynamic characteristics of the TMD carrier. It still stresses the necessity of a diagnostic and therapeutical interdisciplinary and personalized approach, and the importance of a adequate preparation of the health professionals in general, regarding the methods and appropriate cares, destined to patients bearing painful syndromes. The good relation between professional and patient is pointed as one of the most important tools of work that makes possible more efficient and human treatments.